Production of infectious duck hepatitis B virus in a human hepatoma cell line. - Galle, P R (1988)
The differentiated human hepatoma cell line Hep-G2 was transfected with cloned duck hepatitis B virus (DHBV) DNA. Introduction of closed circular DNA into the human liver cells resulted in the production of viral proteins: core antigen was detected in the cytoplasm, and e antigen, a related product, was secreted into the medium. Moreover, viral particles were released into the tissue culture medium which were indistinguishable from authentic DHBV by density, antigenicity, DNA polymerase activity, and morphology. Intravenous injection of tissue culture-derived DHBV particles into Pekin ducks established DHBV infection. In conclusion, transfection of human hepatoma cells with cloned DHBV DNA results in the production of infectious virus, as occurs with cloned human hepatitis B virus DNA. Human liver cells are therefore competent to support production of the avian and mammalian hepadnaviruses, indicating that liver-specific viral gene expression is controlled by evolutionarily conserved mechanisms. This new DHBV transfection system offers the opportunity to rapidly produce mutated DHBV which then can be further investigated in Pekin ducks.